(untitled) (Journal of Atomic and Molecular Sciences, 2018)
By using the time-dependent quantum wave packet method, we report a detailed dynamics study of H exchange reaction H'(²S) + CH(X²Π) → H(²S) + CH'(X²Π) and the isotope effects of H(²S) + CH(X²Π) → C(¹D) + H_2(X¹Σ^+_g) reaction on the 11A BHL potential energy surface. The reaction probabilities and integral cross sections have been obtained for the initial states v = 0 and j = 1 of the reactant molecules. The dense resonance structures in the reaction probabilities at all total angular momentums indicate complex-forming mechanisms for both C + H_2 and H + CH products. A comparison between the results from centrifugal sudden approximation and those from close-coupled calculations demonstrates that the Coriolis coupling effects get more and more pronounced with increasing of J for both H exchange reaction and CH decay reaction. The isotopic D substitution of reactant significantly influences the CH decay reaction. Moreover, it is revealed that the dynamical features such as partial wave contributions to the cross section are substantially different for these two channels.